Comparative aspects of the internal reproductive system of males in species of Melolonthinae, Dynastinae, and Rutelinae (Coleoptera: Scarabaeoidea) from Mexico - Martínez M., Imelda; Rivera-Gasperín, Sara L.; Carrillo-Ruiz, Hortensia; Morón, Miguel A. (Instituto de Ecología, A.C., 2021)
The anatomy of the internal male reproductive systems of 12 species of Melolonthinae (Phyllophaga, Chlaenobia, Macrodactylus, Isonychus), six species of Dynastinae (Cyclocephala), and three species of Rutelinae (Paranomala) (Coleoptera, Scarabaeoidea) of Mexico are described. A total of 350 male specimens representing 21 species were collected. From each species, the reproductive systems were obtained by micro-dissection, placed in a liquid fixative, stained, and drawn to scale. The internal genitalia of each species was described and compared among the species examined. The reproductive system of the Melolonthinae species is comprised of two testicles, each with six follicles, two deferent ducts, two accessory glands, two glandular ducts, an ejaculatory duct, and the aedeagus (not described for any of the species examined). The number of testicular follicles per testicle is as reported in different species of other Scarabaeoidea subfamilies. The length of the accessory glands and the ejaculatory duct varies in the species studied. The ejaculatory bulb is present in all of the species of Dynastinae and Rutelinae examined but in only three species of Melolonthinae.